2021
DOI: 10.2147/ccide.s313587
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Age by Evaluating the Occlusal Tooth Wear in Molars: A Study on Dakshina Kannada Population

Abstract: Purpose: Assessment of teeth to estimate age in the living as well as the dead is well documented in the literature. Though applied in conjunction with other parameters in Gustafson's technique, attrition of teeth solely is an underexplored indicator for age estimation mainly in India. Most of the studies using attrition of teeth have been conducted in bioarchaeology, and in populations where studies are being conducted in forensic contexts, the results are debatable. Thus, the present study aimed to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Furthermore, the error study showed excellent reliability for all the tested variables, which prevented any bias in results. The dental casts were collected from the population aged 18 to 21 years old as the arch dimension growth has stabilized and minimal teeth attrition that may obscure the anatomical landmark in this age group (24). This study was standardized by including only the Class I occlusion sample because dental arch dimensions varied across different types of malocclusions (25,26).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the error study showed excellent reliability for all the tested variables, which prevented any bias in results. The dental casts were collected from the population aged 18 to 21 years old as the arch dimension growth has stabilized and minimal teeth attrition that may obscure the anatomical landmark in this age group (24). This study was standardized by including only the Class I occlusion sample because dental arch dimensions varied across different types of malocclusions (25,26).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 12 incisors and 22 premolars and molars were taken from the upper and lower jaws. The age assigned to individual fossil teeth was determined by conventional methods of age estimation for large ungulates (Greenfield et al 2015, Lewis et al 2021. To prevent a comparison bias due to ontogenetic differences in the morphology of tooth enamel, the analysis was undertaken with teeth from mature individuals of approximately the same age.…”
Section: Methodsmentioning
confidence: 99%
“…A gradual union of the symphysis occurs during childhood and adolescence. Certain skeletal characteristics, like tubercles and mental spines, as well as the degree of fusion, can help with accurate age assessment [5].…”
Section: Introductionmentioning
confidence: 99%